Manipulative Mechanisms in German Economic Discourse: A Study of Publications on Foreign Economic Relations between Germany and China in 2020-2023 - I. A. Shipova; N. V. Badaeva (Научный диалог, 2024)
This study explores the mechanisms of manipulative influence within German-language economic discourse. The empirical material consists of articles from the Köln Institute for Economic Research, detailing external trade cooperation between Germany and China during the years 2020 to 2023. It has been found that metaphors, borrowings, idiomatic expressions, expressive language, and emotives — comprising combinations of evaluative connotations — exert a covert manipulative effect on communication participants. At the grammatical level, the use of adverbs in the superlative degree and modal verbs in the preterite subjunctive form enables the construction of narratives that downplay the significance of China’s successes as an economic competitor. The analysis reveals that manipulation within economic discourse is intentionally obscured, possessing an implicit nature. It has been determined that portraying the Chinese economy in an unequivocally negative light is impractical; however, there are noticeable trends towards diminishing the significance of its successes, negatively evaluating business activity, and exaggerating the perceived threats posed by China to its business partners. The novelty and relevance of this research lie in addressing the techniques of manipulative influence in shaping the linguistic worldview within economic discourse — a perspective that has not yet been explored, as such texts are often considered objective documents grounded in scientific statistical data.